Isolated myocysticercosis of sternothyroid: a rare case - Muskaan, Syeda (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Human cysticercosis is caused by larval stage of Taenia solium manifesting clinically either as neural or extraneural cysticercosis. Neurocysticercosis along with its extraneural counterpart is the usual dictum of disease. Isolated myocysticercosis in absence of neural involvement usually goes undetected or is diagnosed differently due to its rarity. Hence, high suspicion becomes necessary in cases of cystic neck swelling and cysticercosis should always be considered as a probable diagnosis in evaluation of cystic neck lesion.